Antioxidant Capacity and Total Phenolics Changes of Minimally Processed Radish Stored in an Active Modified Atmosphere Under Refrigeration - Incedayi, Bige; Ece Tamer, Canan; Parseker Yonel, Sibel; Utku Copur, Omer (Asian Journal of Chemistry, 2010)
The radish in this research was treated with citric acid (1.5 %) and Ca-ascorbate (0.5 %) + citric acid (1 %) following pre-processes. After centrifugation, the samples were packed in 20 % atmospheric air + 80 % N2 and 20 % atmospheric air + 70 % N2 + 10 % CO2 conditions with 42 μ bi-axially oriented polypropylene (BOPP) film. After 20 days of storage at 4 ± 2 °C, total phenolics, ascorbic acid, total carotenoids content and antioxidant activity of radishes had decreased by 22.65, 24.84, 30.91 and 20.52 %, respectively. More reductions occurred in the control samples that were not treated with any chemicals and they were also rejected by the panelists at the 95 % probability level because of their deleterious texture and appearance. Caascorbate with citric acid treatment with the carbon dioxide enriched atmosphere was found to be more effective with regard to limiting the phenolics, antioxidant activity, weight and total dry matter losses, microbiological spoilage of packaged radishes and prevented organoleptic degradation.